1987
DOI: 10.1037/0097-7403.13.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Associative effects of US preexposure: Modulation of conditioned responding by an excitatory training context.

Abstract: In two experiments we examined factors that contribute to retarded emergence of conditioned responding to a conditioned stimulus (CS) trained in a context in which unsignaled unconditioned stimuli (USs) had previously been administered. In both experiments water-deprived rats were used in a conditioned lick suppression task to measure the conditioned response elicitation potential of the CS and the training context. From Experiment 1 we determined that nonreinforced exposure to the excitatory context after US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
2

Year Published

1988
1988
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 26 publications
7
52
2
Order By: Relevance
“…(2) Long retention intervals between training and testing have produced attenuation ofextinction (Pavlov, 1927) and the CS preexposure effect (Kraemer, Randall, & Carbary, 1991). (3) Posttraining extinction manipulations have successfully revealed latent associations in the CS preexposure effect (Grahame, Barnet, Gunther, & Miller, 1994) and the US preexposure effect (Matzel, Brown, & Miller, 1987). (4) Second-order conditioning procedures have been observed to promote the expression of otherwise unexpressed learning in simultaneous conditioning (Barnet, Arnold, & Miller, 1991;Rescorla, 1980) and trace conditioning deficits (Cole, Barnet, & Miller, 1995b).…”
Section: Resultsmentioning
confidence: 99%
“…(2) Long retention intervals between training and testing have produced attenuation ofextinction (Pavlov, 1927) and the CS preexposure effect (Kraemer, Randall, & Carbary, 1991). (3) Posttraining extinction manipulations have successfully revealed latent associations in the CS preexposure effect (Grahame, Barnet, Gunther, & Miller, 1994) and the US preexposure effect (Matzel, Brown, & Miller, 1987). (4) Second-order conditioning procedures have been observed to promote the expression of otherwise unexpressed learning in simultaneous conditioning (Barnet, Arnold, & Miller, 1991;Rescorla, 1980) and trace conditioning deficits (Cole, Barnet, & Miller, 1995b).…”
Section: Resultsmentioning
confidence: 99%
“…To examine this possibility, in Experiment 4 we extinguished the conditioning context after simultaneous CS-US pairings. Matzel et al (1987) showed that this manipulation reduced a response deficit known to result from an excitatory training context, the US-preexposure deficit.…”
Section: Resultsmentioning
confidence: 99%
“…Conis thought to impede both acquisition of CS-US associa-ditioning was conducted on Days 3-5. On these days, all animals spent tions (e.g ., Randich & LoLordo, 1979) and their expres-20 min in Contexts B, C, and D. Groups F-MC (forward-multipleconsion (e.g., Matzel, Brown, & Miller, 1987). In the present texts) and S-MC (simultaneous-multiple contexts) were placed in the contexts in the order B, C, and D, where they received two randomly experiments we examined the possibility that the associa-distributed3-sec, 0.5-mA, constant-eurrent footshocks in a differentcontive strength of the training context might modulate the text on each day.…”
Section: State University Of New York At Binghamton Binghamton New mentioning
confidence: 99%
See 1 more Smart Citation
“…The decrement of the CR after nonreinforced CS pre-exposure is referred to as latent inhibition (LI; Lubow and Moore 1959), and that after US preexposure is referred to as the US pre-exposure effect (USPEE; Randich and LoLordo 1979). Both phenomena can be studied in numerous species, including human and rodent, and across a variety of associative conditioning procedures (Lubow 1989;Moser et al 2000;Riley and Simpson 2001;Baker et al 1981;Matzel et al 1987;Claflin and Buffington 2006).…”
Section: Introductionmentioning
confidence: 99%